ACQUISITION OF SYNTAX IN CHILD AGED FIVE YEARS (A CASE STUDY RESEARCH) - Dewi Indah Susanti; Jatut Yoga Prameswari (Universitas Indraprasta PGRI, 2020)
Abstract: The purpose of this study was to obtain information about the acquisition of syntactic child aged five year the research is a descriptive qualitative and research method is a case study with content analysis techniques. The subject of this study was one a five-year-old child, whose initial name was HGF, living in the South Jakarta area. Data collection techniques are done by observation and interview methods. Data in the form of audio and video recordings was then transcribed into written form. The data was listened and read repeatedly for later analysis. The most dominant syntactic acquisition results were phrase acquisition, which was62.6% with details of the verb phrase 26.7%, adjunctively phrases 8.6%, noun phrases 12.2%, prepositional phrases 15.1%; acquisition of single sentences was 20.1%; and obtaining compound sentences was 17.3%. Keywords: acquisition, syntax, children.